2013
DOI: 10.4103/0253-7184.120538
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological manifestations in human immunodeficiency virus infected patients: Morphological spectrum with CD4 correlation

Abstract: Background:More than 90% of human immunodeficiency virus (HIV) infected patients develop skin lesions at some time throughout the course of the disease. Several skin diseases have proved to be sensitive and useful indicators of progression of HIV infection. Although these conditions may be seen in general healthy population, their occurrence in patients with acquired immunodeficiency syndrome is often atypical, more severe and explosive.Aims:The present study was carried out to categorize the skin lesions by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 17 publications
(24 reference statements)
3
26
0
1
Order By: Relevance
“…[12] Nichols et al stated that bacterial infections in AIDS were often under represented. [13] In our study we found 08 (13.3%) cases of bacterial infection including Mycobacterium infections as compared to 14 (12.72%) cases of bacterial infection in the study by Sanjay M Chawhan et al [5] Dermatological lesions of tuberculosis (TB) infection are rarely found in Western countries. [14] Various mycobacterium lesions in our study were leprosy (three cases of borderline tuberculoid and one case of tuberculoid leprosy), papulonecrotic tuberculid, scrofuloderma and TB cutis orificialis one each.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…[12] Nichols et al stated that bacterial infections in AIDS were often under represented. [13] In our study we found 08 (13.3%) cases of bacterial infection including Mycobacterium infections as compared to 14 (12.72%) cases of bacterial infection in the study by Sanjay M Chawhan et al [5] Dermatological lesions of tuberculosis (TB) infection are rarely found in Western countries. [14] Various mycobacterium lesions in our study were leprosy (three cases of borderline tuberculoid and one case of tuberculoid leprosy), papulonecrotic tuberculid, scrofuloderma and TB cutis orificialis one each.…”
Section: Discussionmentioning
confidence: 48%
“…In the study by Sanjay M. Chawhan maximum infectious lesions were of viral etiology. [5] Maximum patients showed CD4 counts <350 as studied by other authors.The HPV related lesions were verruca vulgaris, verruca plana and bowenoid papulosis and condylomata accuminata. Muñoz-Pérez et al found no significant difference between the incidence of condyloma acuminata or verruca vulgaris in stage III and stage IV disease or with CD4 counts.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations